Examining peer support and survivorship for African American women with breast cancer. Issue 2 (11th December 2018) - Nicks, Shannon E.; Wray, Ricardo J.; Peavler, Olivia; Jackson, Sherrill; McClure, Stephanie; Enard, Kimberly; Schwartz, Theresa
Abstract: Objective: More than 3.5 million female breast cancer (BrCa) survivors live in the United States, and the number continues to grow. Health status and quality of life among survivors are variable, and African American (AA) survivors suffer disproportionately from BrCa morbidity and mortality. Emerging evidence suggests that peer support is an effective strategy to promote positive survivorship outcomes for AA BrCa survivors. This study aimed to explore the role of peer support in the BrCa experiences of AA survivors. Methods: Working collaboratively with The Breakfast Club, Inc. (BCI), a community‐based BrCa peer support organization, we conducted a quasiexperiment to compare the BrCa experiences of AA survivors. We conducted in‐depth interviews with two survivor groups (N = 12 per group), categorized according to receiving peer support during their BrCa experiences. Results: Survivors who received peer support reported greater access to and utilization of alternative support sources, more capacity to process BrCa‐related stress, and improved quality of life and adjustment to life as BrCa survivors compared with those who did not receive peer support. Conclusions: Peer relationships provide consistent, quality social support. Consistent peer support helps survivors cope with the continued stress of BrCa, with implications for psychosocial health and quality of life. Findings expand our current understanding of peer support and may enable public health and clinical practitioners to better recognize and intervene with those for whom additional support services are needed.